What do people typically do between list items? The nature of attention-based mnemonic activities depends on task context - Vergauwe, Evie (J Exp Psychol Learn Mem Cogn, 2018)
It is commonly assumed that attention-demanding post-encoding processes take place during the free time immediately following encoding of each memory item in a list. These processes are thought to prevent loss of information from working memory (WM). We tested whether inter-item pauses during presentation of a list are used to focus attention (1) on the last-presented memory item or (2) on all items currently in WM, and (3) whether this changes over time. Here, we presented black probe letters between to-be-remembered red letters. Participants judged whether each probe letter corresponded to the last-presented memory item (last-item match group) or to any of the memory items presented up to that point in the list (any-item match group). To examine mnemonic processing as a function of time, the delay between the to-be-remembered letter and the following probe was manipulated in three experiments. When pre-probe delays and inter-item intervals were relatively short (Experiment 1), recall performance was observed to be better in the last-item match group and this did not change as a function of the duration of the delay before the probe. When pre-probe delays and inter-item intervals were longer however (Experiment 2), this disruptive effect of Any-item match instructions was no longer observed. This pattern was found again in Experiment 3 and suggests that the nature of the attention-demanding post-encoding processes taking place in between memory items depends on task context in a systematic manner. The results are discussed in terms of previously proposed attention-demanding processes; specifically, consolidation and refreshing.